Pengaruh ROA, ROE, dan NPM Terhadap Pertumbuhan Laba Pada Perusahaan Sektor Industri Barang Konsumsi Yang Terdaftar di Bursa Efek Indonesia - Anggi Maharani Safitri; Mukaram (Jurnal Riset Bisnis dan Investasi, 2018)
The purpose of this research to analyze the effect of return on asset, return on equity, net profit margin on profit growth partially of consumer goods industry companies that were listed in Indonesia stock exchange period 2010-2015. Data used in this research was secondary data as 31 samples with saturated sampling. Multiple linear regression, classical assumption test and determination coefficient used to analyze the relation between independent and dependent variable. The findings of this research identified that return on asset on profit growth was significance and negative of -2.115 and p-value of 0.034. Then, return on equity on profit growth was no significance of 0.684 and p-value of 0.186. While net profit margin on profit growth was significance and positive of 2.349 and p-value of 0,036.